Autophagy Induced Accumulation of Lipids in pgrl1 and pgr5 of Chlamydomonas reinhardtii Under High Light - Chouhan, Nisha; Devadasu, Elsinraju; Yadav, Ranay Mohan; Subramanyam, Rajagopal (Frontiers in Plant Science, 2022)
Chlamydomonas (C.) reinhardtii is a potential microalga for lipid production. Autophagy-triggered lipid metabolism in microalgae is not being studied so far from a mutant of proton gradient regulation 1 like (PGRL1) and proton gradient regulation 5 (PGR5). In this study, C. reinhardtii cells (wild-type CC124 and cyclic electron transport dependant mutants pgrl1 and pgr5) were grown photoheterotrophically in high light 500 µmol photons m-2 s-1, where pgr5 growth was retarded due to an increase in ROS. The lipid contents were increased; however, starch content was decreased in pgr5. Further, the Nile Red (NR) fluorescence shows many lipid bodies in pgr5 cells under high light. Similarly, the electron micrographs show that large vacuoles were formed in high light stress despite the stacks of grana structure. We also observed increased production of reactive oxygen species, which could be one reason the cells underwent autophagy. Further, a significant increase of autophagy ATG8 and detections of ATG8-PE protein was noticed in pgr5, a hallmark characteristic for autophagy formation. Consequently, the triacylglycerol (TAG) content was increased due to diacylglycerol acyltransferases (DGAT) and phospholipid diacylglycerol acyl-transference (PDAT) enzymes' expression, especially in pgr5. Here the TAG synthesis would have been obtained from degraded membrane lipids in pgr5. Additionally, mono, polyunsaturated, and saturated fatty acids were identified more in the high light condition. Our study shows that the increased light induces the reactive oxygen species, which leads to autophagy and TAG accumulation. Therefore, the enhanced accumulation of TAGs can be used as feedstock for biodiesel production and aqua feed.